2011
DOI: 10.5209/rev_sjop.2011.v14.n2.6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Processes, Working Memory, Phonological Awareness, Naming Speed, and Early Arithmetic Achievement

Abstract: This study identified the cognitive processes that underlie the individual differences in early mathematical performance in elementary school children. Taking into account the Baddeley framework multicomponent model, the inhibitory processes, working memory, phonological awareness, and naming speed are considered to be related to early math learning. To examine this relationship, we compared the performance of a total of 424 typically developing middle-class children, aged between 4 and 7 years in a battery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
1
18
0
3
Order By: Relevance
“…Evidence of a distinction between these two factors has been found using factor analysis (Oberauer et al, 2003), which is why this distinction is employed in this study. Visuospatial updating has consistently been found to be associated with mathematical performance (St Clair-Thompson and Gathercole, 2006), whereas verbal updating has been found to have a unique association with mathematical skills in some studies (Jarvis and Gathercole, 2003;Navarro et al, 2011), but not in others (St Clair-Thompson and Gathercole, 2006).…”
Section: Relations Between Working Memory and Mathematical Performancementioning
confidence: 94%
“…Evidence of a distinction between these two factors has been found using factor analysis (Oberauer et al, 2003), which is why this distinction is employed in this study. Visuospatial updating has consistently been found to be associated with mathematical performance (St Clair-Thompson and Gathercole, 2006), whereas verbal updating has been found to have a unique association with mathematical skills in some studies (Jarvis and Gathercole, 2003;Navarro et al, 2011), but not in others (St Clair-Thompson and Gathercole, 2006).…”
Section: Relations Between Working Memory and Mathematical Performancementioning
confidence: 94%
“…Oakhill and Kyle (2000) have found that central executive function plays an important role in phonological awareness tasks as well (e.g., the rhyme oddity task). Navarro et al (2011) also found a strong correlation between central executive and phonological awareness tasks in a group of 424 typically developing children (age: 4 to 7 years). Thus, successful phonemic deletion is also contingent upon the capacity of verbal working memory to store the target word and locate the phoneme to be deleted.…”
Section: Common Operational Demands Of Phonological Awareness and Vermentioning
confidence: 97%
“…Stroop tasks have frequently been employed in studies exploring the relationship of inhibition with mathematics performance (e.g. Bull and Scerif 2001;Lemaire and Lecacheur 2011;Monette et al 2011;Navarro et al 2011;St Clair-Thompson and Gathercole 2006;Szucs et al 2013;Van der Ven et al 2012;Visu-Petra et al 2011).…”
Section: Types Of Inhibition Taskmentioning
confidence: 99%